2000
DOI: 10.1007/s002680010229
|View full text |Cite
|
Sign up to set email alerts
|

99mTc‐sestamibi Scintigraphy and Cell Cycle in Parathyroid Glands of Secondary Hyperparathyroidism

Abstract: Double-phase parathyroid MIBI ((99m)Tc-sestamibi) was performed in 27 patients with secondary hyperparathyroidism (SPT). Focal areas of increased uptake were scored for intensity on a three-point scale. All patients underwent subtotal parathyroidectomy (SPTx), and a total of 78 glands were removed at operation. Blood was obtained from the jugular vein before and after SPTx to measure the parathyroid hormone (PTH) levels. The volume and weight of the glands were calculated. The tissue was divided, with one aliq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
36
0
5

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 17 publications
1
36
0
5
Order By: Relevance
“…The same study found higher degrees of uptake to be correlated with the G 2 /S (active growth) phase. In our present study, MIBI detected hyperplastic glands in 88.8% of the cases, a sensitivity similar to that found previously [10]. There are many important factors that need to be taken into account when analysing false-negative MIBI results.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…The same study found higher degrees of uptake to be correlated with the G 2 /S (active growth) phase. In our present study, MIBI detected hyperplastic glands in 88.8% of the cases, a sensitivity similar to that found previously [10]. There are many important factors that need to be taken into account when analysing false-negative MIBI results.…”
Section: Discussionsupporting
confidence: 74%
“…We obtained similar results in a study of 116 patients, in whom we demonstrated a positive association between PTH levels and MIBI uptake (unpublished data). Moreover, Torregrosa et al [10] showed a positive correlation between MIBI uptake in the parathyroid glands and the phases of the cell cycle. The same study found higher degrees of uptake to be correlated with the G 2 /S (active growth) phase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that glands with nodular growth patterns are heavier and show higher proliferative activity than diffusely hyperplastic glands [17,18]. Torregrosa et al demonstrated that 99m Tc MIBI scintigraphy accurately reflects the functional status of the hyper-plastic parathyroid glands, with higher uptake grades correlating with the active growth phase [19].…”
Section: Discussionmentioning
confidence: 99%
“…In the cases presented there were no histological signs of oxyphil cells, and the influence of other factors cannot be excluded. Variability of radiotracer uptake in parathyroid adenomas is another factor reported in addition to oxyphil cell content to which differences in perfusion and metabolic activity, P-glycoprotein expression, and multidrug resistance-related protein expression, and cell cycle may be attributed [7][8][9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%